Public knowledge of cardiovascular disease and response to acute cardiac events in three cities in China and India. Issue 1 (29th June 2017) - Duber, Herbert C; McNellan, Claire R; Wollum, Alexandra; Phillips, Bryan; Allen, Kate; Brown, Jonathan C; Bryant, Miranda; Guptam, R B; Li, Yichong; Majumdar, Piyusha; Roth, Gregory A; Thomson, Blake; et al.
Abstract : Objective: To inform interventions targeted towards reducing mortality from acute myocardial infarction (AMI) and sudden cardiac arrest in three megacities in China and India, a baseline assessment of public knowledge, attitudes and practices was performed. Methods: A household survey, supplemented by focus group and individual interviews, was used to assess public understanding of cardiovascular disease (CVD) risk factors, AMI symptoms, cardiopulmonary resuscitation (CPR) and automated external defibrillators (AEDs). Additionally, information was collected on emergency service utilisation and associated barriers to care. Results: 5456 household surveys were completed. Hypertension was most commonly recognised among CVD risk factors in Beijing and Shanghai (68% and 67%, respectively), while behavioural risk factors were most commonly identified in Bangalore (smoking 91%; excessive alcohol consumption 64%). Chest pain/discomfort was reported by at least 60% of respondents in all cities as a symptom of AMI, but 21% of individuals in Bangalore could not name a single symptom. In Beijing, Shanghai and Bangalore, 26%, 15% and 3% of respondents were trained in CPR, respectively. Less than one-quarter of participants in all cities recognised an AED. Finally, emergency service utilisation rates were low, and many individuals expressed concern about the quality of prehospital care. Conclusions: Overall, we found low to modest knowledge of CVD risk factors and AMI symptoms, infrequent CPR training and little understanding of AEDs. Interventions will need to focus on basic principles of CVD and its complications in order for patients to receive timely and appropriate care for acute cardiac events.